Association Between Triglyceride Glucose Index and Risk of New-Onset Diabetes Among Chinese Adults: Findings From the China Health and Retirement Longitudinal Study - Chen, Chao-lei; Liu, Lin; Lo, Kenneth; Huang, Jia-yi; Yu, Yu-ling; Huang, Yu-qing; Feng, Ying-qing (Frontiers in Cardiovascular Medicine, 2020)
The triglyceride glucose (TyG) index has been proposed to be a surrogate of insulin resistance. In the present study, we aimed to examine the relationship between TyG index and the risk of incident diabetes in middle-age and older adults in China using nationally representative data from the China Health and Retirement Longitudinal Study 2011-2015. Information on socio-demographics, medical background, anthropometric measurement and laboratory information were collected. The association between TyG index and diabetes was examined by Cox proportional hazards models and restricted cubic spline regression, and the results were presented in hazard ratio (HR) with 95% confidence interval (CI). Subgroup analyses were also conducted to examine potential interactions between demographics and TyG index. Among 7428 participants, 791 (10.6%) of them developed diabetes over 3.4 years of follow-up. The multivariate HR for every SD increment in TyG index was 1.22 (95% CI, 1.14-1.31). When comparing to the lowest quartile of TyG index, the multivariate HRs for new-onset diabetes were 1.22 (0.96-1.54) for Q2, 1.61 (1.28-2.01) for Q3, and 1.73 (1.38-2.16) for Q4 (P for trend < 0.001). The restricted cubic spline regression also showed a linear association. No interaction was found between subgroup variables and the association bewteen TyG index and the risk of diabetes. In conclusion, higher TyG index associated with the elevated risk of new-onset diabetes in middle-aged and older adults.